Letters to Doubting Thomas : a Case for the Existence of God. - Layman, C. Stephen (Oxford University Press, USA, 2006)
When people encounter an argument for or against God's existence, it often raises more questions than it answers. In Letters to Doubting Thomas, C. Stephen Layman offers a fresh, insightful approach to the issue of God's existence--a way to organize what can seem like a blizzard of claims and concepts--bringing clarity to a debate often mired in confusion. Layman explores the evidence for the existence of God in a series of fictionalized letters between two characters--Zachary, a philosopher, and Thomas, an old college friend who appeals to Zach for help in sorting out his thoughts about God.